The Relationship between Motivation and Economical Background in Learning English for Horse Keeper (Komunitas Kuda Tunggang) in Gedongsongo Temple - Yuniarti, Nanda Eka; Ifadah, Muhimatul (Universitas Muhammadiyah Semarang, 2018)
Indonesia tourism is experiencing a rapid increase each year. Some tourism providers need skillful workers to adapt with it. However, as the local citizen, Indonesian people are being influenced with this phenomena. In Gedongsongo Temple, the horse keeper (KKT) are also become object who need to develop themselves to face the competitive and massive trends. This study aims to determine the motivation of the horse keeper in learning English. To obtain the data, a descriptive qualitative approach. The result shows that the motivation of the horse keeper was low proved by the process and the involvement during the program, due to internal and external factors. However economical factor become the main reason for them to not enrich their English skill.